Left rostrolateral prefrontal cortex lesions reduce suicidal ideation in penetrating traumatic brain injury. (February 2020) - Pardini, Matteo; Grafman, Jordan; Raymont, Vanessa; Amore, Mario; Serafini, Gianluca; Koenigs, Michael; Krueger, Frank
Abstract : Objectives: The objective of this study is to evaluate the relationship between suicidal ideation (SI), structural brain damage, and cognitive deficits in patients with penetrating traumatic brain injury (pTBI). Methods: Vietnam War veterans ( n = 142) with pTBI to the prefrontal cortex (PFC) underwent combination of neuropsychological and psychiatric examinations and non-contrast CT brain scan. Patients were divided into SI positive (SI+) and SI negative (SI−) groups according to the SI item of the Beck Depression Inventory. Results: Lesions to the left rostrolateral PFC (rlPFC) were associated with a lower risk of SI independent of depression and global functioning. Left rlPFC lesion also reduced abstract reasoning skills, which mediated the lesion effects on suicide ideation. Conclusions: The left rlPFC plays a crucial role in SI independently of depression and global functioning.